Exploring issues in the conduct of website searching and other online sources for systematic reviews: how can we be systematic?. Issue 1 (December 2016) - Stansfield, Claire; Dickson, Kelly; Bangpan, Mukdarut
Abstract Websites and online resources outside academic bibliographic databases can be significant sources for identifying literature, though there are challenges in searching and managing the results. These are pertinent to systematic reviews that are underpinned by principles of transparency, accountability and reproducibility. We consider how the conduct of searching these resources can be compatible with the principles of a systematic search. We present an approach to address some of the challenges. This is particularly relevant when websites are relied upon to identify important literature for a review. We recommend considering the process as three stages and having a considered rationale and sufficient recordkeeping at each stage that balances transparency with practicality of purpose. Advances in technology and recommendations for website providers are briefly discussed.